2019
DOI: 10.1097/aud.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Instruments for Children With Cochlear Implants: Development of Child and Parent-Proxy Measures

Abstract: CI-specific HRQoL instruments have now been developed for school-age children with CIs, with an accompanying parent-proxy version. After a psychometric validation, these CI-specific measures will enable us to track long-term outcomes, evaluate the efficacy of interventions to improve CI use (e.g., single versus bilateral implantation, AV therapy, maternal sensitivity training), and provide a profile of the "whole child's" functioning to facilitate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 47 publications
1
36
0
1
Order By: Relevance
“…Severe-to-profound hearing loss, even in the era of cochlear implantation, leads to a cascading set of challenges for young children, including problems with visual attention and development 5of behavioral control. These issues likely affect children’s daily functioning at home and at school, and their overall health-related quality of life (Hoffman, Cejas, & Quittner, 2016). Currently, cochlear implant teams do not focus on these other dimensions of development and thus, may not be positioned to address them.…”
Section: Discussionmentioning
confidence: 99%
“…Severe-to-profound hearing loss, even in the era of cochlear implantation, leads to a cascading set of challenges for young children, including problems with visual attention and development 5of behavioral control. These issues likely affect children’s daily functioning at home and at school, and their overall health-related quality of life (Hoffman, Cejas, & Quittner, 2016). Currently, cochlear implant teams do not focus on these other dimensions of development and thus, may not be positioned to address them.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven met 15 or more of the 32 checklist criteria, including greater coverage of information on sampling, data collection and analysis than other papers. Four studies (three of these being those identified as meeting a high number of criteria on the COREQ) reported following FDA guidelines for measure development [19,21,46,52] and a further study (also highly detailed) mentioned following the COREQ guidelines for reporting [20]. Twenty of the 37 papers stated that they had ethical approval for the qualitative study, with twelve mentioning gaining informed consent (or assent) from research participants.…”
Section: Strengths In Reportingmentioning
confidence: 99%
“…Undoubtedly, the HRQoL of children aroused the interest of researchers due to its emphasis on the components of children's healthy well-being and, particularly, the influence treatment had on the quality of life (QoL) (Berger & Karabenick, 2016;Karimi & Brazier, 2016). This historical perspective helped to explain how this ambitious and research effort notion remained consistent (Hoffman, Cejas, & Quittner, 2018).…”
Section: Importance Of the Problemmentioning
confidence: 99%